2008
DOI: 10.1016/j.neuron.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Seeking Habits Depend upon Dopamine-Dependent Serial Connectivity Linking the Ventral with the Dorsal Striatum

Abstract: A neuroanatomical principle of striatal organization has been established through which ventral domains, including the nucleus accumbens, exert control over dorsal striatal processes mediated by so-called "spiraling," striato-nigro-striatal, circuitry. We have investigated the functional significance of this circuitry in the control over a cocaine-seeking habit by using an intrastriatal disconnection procedure that combined a selective, unilateral lesion of the nucleus accumbens core and infusion of a dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
510
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 645 publications
(556 citation statements)
references
References 60 publications
(87 reference statements)
41
510
2
3
Order By: Relevance
“…Although either manipulation on its own was without effect, the combined procedures selectively decreased cocaine seeking in extensively trained rats but not in rats that had undergone only moderate training (23). Together with our study, these findings underline the functional significance of the network interaction between the VMS and the DLS in drugrelated behavior.…”
Section: Dopamine Signaling In the Sensorimotor Striatum Emerges Beforesupporting
confidence: 79%
See 2 more Smart Citations
“…Although either manipulation on its own was without effect, the combined procedures selectively decreased cocaine seeking in extensively trained rats but not in rats that had undergone only moderate training (23). Together with our study, these findings underline the functional significance of the network interaction between the VMS and the DLS in drugrelated behavior.…”
Section: Dopamine Signaling In the Sensorimotor Striatum Emerges Beforesupporting
confidence: 79%
“…This progressive involvement of the DLS in drug seeking has been linked to circuitry that connects the VMS to the DLS by a serial disconnection study that demonstrated that the development of advanced cue-controlled drug-seeking behavior is dependent on intact VMS circuitry (23). Therefore, to test whether the later-emerging phasic dopamine signal in DLS reported in the present study was dependent upon antecedent activity in the VMS circuitry, we mimicked a disconnection of the VMS from DLS on one side of the brain with a unilateral excitotoxic lesion of the nucleus accumbens core (VMS) by infusing quinolinic acid before training (23), leaving the other side intact. Voltammetric microsensors were implanted bilaterally in the DLS (n = 17), permitting within-subject comparison of emergent DLS dopamine transmission between hemispheres, one hemisphere having an intact and the other a lesioned VMS (see Fig.…”
Section: Dopamine Receptors In the Dls Are Necessary For Discriminatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The striatum has long been implicated in learning (Atallah, Lopez-Paniagua, Rudy, & O'Reilly, 2007), and connectivity between the ventral and dorsal striatum is essential for learning (Belin & Everitt, 2008). In a study by den Ouden et al (2009), the putamen (and dorsolateral prefrontal cortex) have been implicated in the acquisition of cue-target learning over time as modeled by a Rescorla-Wagner model, and shown to be sensitive to unexpected outcomes even when those are task irrelevant and learned incidentally, as is the case in the current study.…”
Section: A Common System For Category and Location Regularitysupporting
confidence: 49%
“…It has been suggested that after extended training, habits become deeply engrained by shifting further dorsally in the corticostriatal loops (Belin and Everitt, 2008;Willuhn et al, 2012). Using cyclic voltammetry and a behavioural paradigm similar to sign-tracking paradigm, Clark et al (2013) examined changes in dopamine release in the nucleus accumbens core during the acquisition and maintenance of a Pavlovian conditioned approach response (i.e.…”
Section: Shifts Towards Model-free Learning In Addictionmentioning
confidence: 99%